Atypical Clinical Course in a Patient with Acute Carotid Artery Dissection - Çiğdem DENİZ; Tuğçe ÖZDEMİR GÜLTEKİN; Gözde ERYİĞİT BARAN; Ayşe ARALAŞMAK; Ömer GÖKTEKİN; Talip ASİL (Bezmiâlem Science, 2018)

(untitled)
Extracranial or intracranial artery dissections are more frequently reported because of cerebrovascular disease occurring in young adults. This condition is more likely to be associated with permanent morbidity and mortality. While anti-coagulant medications are commonly used for its treatment, an increased use of intravenous thromobolytic agents and endovascular treatments has also been reported. In this paper, the case of a patient with an atypical clinical course following thrombolytic treatment for acute extracranial internal carotid artery (ICA) dissection is presented in the context of a discussion regarding the safety and efficacy of aggressive treatment for extracranial arterial dissections.